PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG - Abdurrahmat Fathoni; Shofwan Hendryawan; Ari Arifin; Denny (JRPA - Journal of Regional Public Administration, 2019)
The purpose of the research conducted is to find out the influence of work discipline on work productivity in the South Sumedang District Office of Sumedang Regency and to find out the relationship of work discipline to work productivity in the South Sumedang District Office of Sumedang Regency. The method used in this research is a quantitative research method that is used in research based on the philosophy of positivism with the aim of testing established hypotheses. In this study, researchers used inferential descriptive data analysis techniques to describe or describe the data that has been collected as is by making conclusions that apply to the public. The sampling technique used is a saturated sampling technique, with a population of 27 people. Based on the results of the study, it can be seen that the work discipline in the South Sumedang District Office of Sumedang Regency has reached 79.72% and the figure is categorized as Good, as well as the level of work productivity in the South Sumedang District Office of Sumedang Regency which reaches 81.32% and the figure is categorized as Good. The relationship of work discipline with work productivity in the South Sumedang District Office of Sumedang Regency with a correlation coefficient value of 0.87 is in a very strong category. While the influence of work discipline with work productivity in the South Sumedang District Office of Sumedang Regency reached 62% while the remaining 38% was influenced by other factors that were not studied by researchers called epsilon factor.